Detection of extended-spectrum beta-lactamases in Pseudomonas aeruginosa and Acinetobacter baumanniiand their prevalence in Intensive care unit of a tertiary care hospital - Dr. Charanjeev Kaur; Dr. Sarbjeet Sharma; Dr. Poonam Sharma (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Pseudomonas aeruginosa and Acinetobacter baumannii have been known to cause variety of infections, among patients admitted in Intensive Care Unit.Non fermenting Gram‑negative bacilli are developing resistance to commonly used antibiotics therefore are becoming difficult to treat Among various enzymes produced by bacteria which lead to drug resistance, extended‑spectrumbeta‑lactamase (ESBL) enzymesis one of the important mechanism of drug resistance. Thisstudy that was conducted a) To detect multidrug-resistant P. aeruginosa and A. baumanniiin patients admitted in ICU patients. b) To determine the prevalence of ESBL producing clinical isolates of Pseudomonas aeruginosa and Acinetobacter sp. in the ICU of the tertiary care hospital. Material and Methods: The study was performed in the microbiology department of a North Indian rural tertiary care hospital (Sri Guru Ram Das Institute of Medical Sciences and Research, Amritsar, India) over a period of one year (January2012 to December 2012). The study included 100 isolates each of Acinetobacter baumannii & P. aeruginosa. Identification of both organisms was done using the standard microbiological techniques as described by Colle et al 1996.The antimicrobial susceptibility testing was performed by Kirby Bauer disc diffusion method. To detect ESBL producing isolates phenotypicaly, Disc approximation test was performed. Results: Out of 200 isolates, 100 each of A. baumannii and P. aeruginosa, weobtained 82 isolates from ICU,57 &25 A .baumannii and P. aeruginosa respectively. Among these 57A. baumannii isolates 89.47%isolates were resistant to Ceftazidime and among these 33.33%isolates were ESBL producers.Of 25 P.aeruginosa isolatesobtained from ICU84 % were found to beresistant to ceftazidime by antibiotic sensitivity testing.Among these44% were ESBL producers. Conclusion: Our results showed high prevalence ofNon fermenting gram negative bacilli in ICU patient’s samples, which were multidrug resistant and producers of Extended spectrum Beta lactamase enzymes.